2000
DOI: 10.1002/(sici)1520-6300(200001/02)12:1<17::aid-ajhb3>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Color-blindness in Calabria (Southern Italy): A north-south decreasing trend

Abstract: The frequency of color‐blindness (CB) in 13,072 males from 409 towns in Calabria is 5.42%. Regional variation in CB within the three provinces of Calabria was studied: Cosenza (northern), Catanzaro (central), and Reggio Calabria (southern). There is a decreasing trend of mean frequencies of CB from Cosenza to Reggio Calabria through Catanzaro: 6.23%, 4.65%, and 3.43%, respectively. The mean frequencies do not take into account the two ethnic minorities present in Calabria: Albanians and Grecanicans. The freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 15 publications
2
8
0
Order By: Relevance
“…As we have commented above, relative high genetic distances between neighbouring populations were found between Cosenza and (1) Catanzaro and (2) Reggio di Calabria and between Ibiza and (1) Majorca and (2) Valencia. The results support the hypothesis that the genetic differentiation of the Ibiza and Cosenza populations is a result of their particular demographic histories [15,16,23]. The Moroccan population showed a high level of differentiation in relation to the other populations, even to those that are geographically close to Morocco (Western side of the Mediterranean basin).…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…As we have commented above, relative high genetic distances between neighbouring populations were found between Cosenza and (1) Catanzaro and (2) Reggio di Calabria and between Ibiza and (1) Majorca and (2) Valencia. The results support the hypothesis that the genetic differentiation of the Ibiza and Cosenza populations is a result of their particular demographic histories [15,16,23]. The Moroccan population showed a high level of differentiation in relation to the other populations, even to those that are geographically close to Morocco (Western side of the Mediterranean basin).…”
Section: Resultssupporting
confidence: 83%
“…Several authors [9,10] have suggested the existence of a north-south genetic "barrier" in the western part, and no consensus on the current genetic landscape has been established [4,29,30]. Some isolated populations with deviating genetic differentiation have been described [5,6,16,23]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Calabrian life tables from 1940s onward do not show significant differences with respect to the average Italian mortality data. However, we may suppose that, based on its socio economic conditions, 24 life expectancy in Calabria at the beginning of the XX century was lower than in the rest of Italy, where, on turn, it was lower than in northern European countries. 25 Therefore we can expect that this point does not affect our results or led to an underestimate of survival advantage with respect to the general population cohorts.…”
Section: Discussionmentioning
confidence: 95%
“…It is especially important to evaluate genetic sub-structure in the western Mediterranean area, due to the existence of some geographical and/or cultural isolates such as Balearic populations [24,37] and Calabrian populations [36]. We studied the genetic constitution of seven western Mediterranean populations (Valencia and two Balearic Islands, from eastern Spain, Sicily and three provinces in the Calabria region, southern Italy) with the aim of establishing a Y-STR haplotype regional database and to evaluate sub-structuring of geographical sub-sets in this Mediterranean region.…”
Section: Introductionmentioning
confidence: 99%